A survey of newly recruited nurses' perception and needs for scene simulation teaching of critical care hepatology (新入职护士对肝脏疾病急危重症情景模拟教学认知及需求的调查) - NIAN Guihong (年桂红); LU Lihua (陆丽华); ZHU Hengmei (朱恒美) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the perception and needs for teaching of hepatology critical care among newly recruited nurses, and to provide reference for implementation of scene simulation training method in clinical teaching of critical care hepatology. Methods Convenience sampling was used to enroll 70 newly recruited nurses in the Department of Hepatology. A survey of using self-made questionnaire about perception and needs for scene simulation teaching was conducted. Results Five items with highest score was improving the first-aid ability in management of critical illness (4. 43±0. 50), improving the first-aid experience(4. 40±0. 55), enhancing the theory knowledge about critical care medicine(4. 39±0. 62), practicing skills of linking theory to practice(4. 31±0. 50)and improving motivation(4. 30±0. 60). Nurses had the highest demand for training of upper gastrointestinal hemorrhage management, and 91. 43% of nurses hoped to have more training opportunities, and duration of training would be 40～60 min per course. Conclusion The findings of the survey indicated a higher level of cognition on scene simulation teaching of critical care hepatology among newly recruited nurses, and there was an urgent need of first-aid knowledge and skills training. A purposive training program using scene simulation teaching method should be carried out in clinical teaching of critical care hepatology, in order to improve newly recruited nurses' emergency and critical care skills and ability to deal with emergencies. (目的 调查分析新入职护士对肝脏疾病急危重症教学认知状况及需求, 为进一步开展肝脏疾病急危重症情景模拟教学培训提供参考。方法 采用方便抽样法, 应用自制新入职护士对肝脏疾病急危重症情景模拟教学认知及需求调查问卷, 对医院2020年1月-12月肝脏疾病科室新入职的70名护士进行问卷调查。结果 急危重症情景模拟教学的认知调查中得分最高的前5项分别是: "提高临床急危重症急救技能操作能力"得分(4. 43±0. 50)分, "提高临床急救经验"得分(4. 40±0. 55), "增加对急危重症理论知识的巩固"得分(4. 39±0. 62), "锻炼理论联系临床实际的能力"得分(4. 31±0. 50), "提高主观能动性"得分(4. 30±0. 60)。对急危重症情景模拟教学的技能培训需求结果显示"上消化道出血"位列第一, 91. 43%新入职护士希望参加相关培训, 培训时间以40～60min最为适宜。结论 新入职护士对肝脏疾病急危重症情景模拟教学整体认知度高, 对急危重症情景模拟相关急救知识技能培训需求较高。科室培训应有针对性地开展肝脏疾病急危重症情景模拟培训方案, 进一步提升新入职护士的急危重症急救技能, 使其掌握操作流程, 提高应急处置能力。)